Analisis Dinasti Politik di Indonesia: Dilema Etika Demokrasi dan Relevansinya dalam Keadilan Politik Indonesia - Hauyyine Sucipto; Sergio Sitinjak; Ikhsan Sujatmoko (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2023)
This research aims to analyze the phenomenon of dynastic politics in Indonesia which is a challenge in political ethics because it conflicts with democratic principles which prioritize people's sovereignty. This practice can hinder the political participation of the wider community and create a political oligarchy. This phenomenon of dynastic politics, which is thick with elements of kinship, has implications for the dynamics of political parties in the Indonesian government structure. Through qualitative research methods, this research provides a deeper understanding of the factors that influence dynastic politics and their impact on the government system in Indonesia. By using normative ethics, this research evaluates the norms and values involved in the case of dynastic politics. Dynastic politics in Indonesia not only influences the structure of political decisions, but also poses a threat to the foundations of democracy and the principles of political ethics. Therefore, substantive changes in the government system and expanded public participation are needed to overcome the negative impacts of dynastic politics and ensure a more just and accountable government.